Seasonal variations of childhood Guillain-Barre Syndrome in South west Iran - Momen, Ali A.; Shakurnia, Abdolhussein; Sarrami, Mahsa (Journal of the Faculty of Medicine Baghdad, 2018)
Background: It was found that the occurrence of Guillain-Barre Syndrome (GBS) varies in respect tothe month and season; this variation has not been adequately studied.Objective: To determine the month and seasonal variation of GBS in children in the Khuzestanprovince, south west Iran, during a 10-year period (2006-2015).Patients and methods: We extracted data retrospectively from acute flaccid paralysis committeefrom healthcare centers in all cities of the province, over a 10-year period (from January 1, 2006 toDecember 31, 2015). In this study all children under 15 years of age with Guillain-Barre syndromewere surveyed. In order to compare the frequency of GBS in different seasons and months we used theChi Square test.Results: From 187 cases of GBS, 101 (54%) were males, 86 (46%) females with sex ratio 1.17:1. Themean age of the children was 5.39 ± 4.02 years. The highest occurrence of GBS was observed inautumn (32.1%) followed by winter (27.3%). The highest number of cases (28; 15%) occurred inDecember and the lowest (8; 4.3%) in September. There was seasonal (P=0.006) and monthly(P=0.036) variation in occurrence of GBS throughout the year with more prevalence in autumn ,September and December.Conclusion: Our study showed that there is a significant monthly and seasonal variation in childrenwith GBS in Khuzestan province.